Parental and adolescents’ perspectives on environmental predictors of active commuting to school – findings from the ARRIVE mixed-methods study - Clara Tristram; Isabel Marzi; Franziska Beck; Katharina Diehl; Denise Renninger; Yolanda Demetriou; Claus Krieger; Anne Kerstin Reimers (Frontiers in Built Environment)
BackgroundActive commuting to school (e.g., walking or cycling) can contribute to an increase in daily physical activity time of adolescents which is associated with positive health effects. However, it is known that the perceived barriers related to the physical and social environment hinder adolescents in participating in active commuting. To obtain more information about these barriers, and therefore be able to address them in the future, the present study aims to investigate how parents’ and adolescents’ perception of the physical and social environment is associated with (active) commuting to school.MethodsThe ARRIVE study consists of a quantitative online survey with parent-adolescent dyads (N = 517) followed by qualitative interviews with adolescents and parents (N = 32). The quantitative part examined adolescents’ travel behaviour to and from school and its predictors. The qualitative part sought to explore the decision-making process in families regarding transport mode choice. To evaluate predictors of active commuting to and from school binary logistic regression analysis and qualitative content analysis were performed.ResultsIn the quantitative part, we found that adolescents and parents perceive especially having much luggage to carry as crucial for adolescents’ active travel. Besides this barrier on active commuting to and from school found in the questionnaires, parents and adolescents reported lack of social support, weather, convenience, lack of traffic safety and getting a lift as barriers in the interviews.ConclusionWe found differences and similarities in the perceived barriers of active commuting regarding the physical and social environment between adolescents and parents. To encourage adolescents to actively commute to school, the perception of the physical and social environment, especially from parents, be taken into account.